DESIGN RULES OPTIMIZATION IN DESIGNING OF SHEET METAL PART - Taufik, ,; Shajahan, Maidin; Sivarao, Subramonian (2008)
This research addressed the design rules optimization of sheet metal part for typical industry that will aid designers through design process stage. Design is the most important and an expensive stage in the product development process. Design of sheet metal parts is greatly dependent on manufacturing experiences, which have to be documented and incorporated in design process stage. It would eliminate frequent redesign of part, after being assessed as infeasible or costly for manufacture in design stage. Through design of experiment would reduce a number of design rules significantly. This research aim to optimize a comprehensive set of design rules for design of sheet metal part and develop a design of experiment (DOE) for implementing inter-feature design rule for reducing infeasible design, cost and production cycle times.